Conversations with Jay Parini - Lackey, Michael (Literary conversations series., 2014)
"This book contains the most important interviews with Jay Parini, who is best known for his 1990 The Last Station, a multi-perspective novel about Leo Tolstoy's last year. But he has also published numerous volumes of poetry; biographies of William Faulkner, Robert Frost, and John Steinbeck; novels; and literary and cultural criticism. Parini's work is valuable not just because of its high quality and intellectual range. It is crucial for understanding late-20th and early-21st century literature more generally, as Parini not only engages in a lively conversation with other prominent writers, but also was close friends with so many of these authors. He has openly written poems in conversation with such writers as Robert Penn Warren, Gore Vidal, Jorge Luis Borges, and others. He has had an ongoing conversation with many literary friends over the years--Alastair Reid, Seamus Heaney, Anne Stevenson, Ann Beattie, Julia Alvarez, Peter Ackroyd, A.N. Wilson, and countless others. His life often seems like a seminar table, with friends gathered, talking, trading stories. These interviews will give scholars a more comprehensive understanding of his work as a poet, scholar, public intellectual, literary critic, intellectual historian, biographer, novelist, and biographical novelist. More importantly, these interviews will contribute to our understanding of the history of ideas, the condition of knowledge, and the state of literature, which Parini has played an important role in shaping"--